The Oxford encyclopedia of the Reformation - Hillerbrand, Hans J. (Oxford reference online Oxford digital reference shelf, 2005)
The Oxford Encyclopedia of the Reformation is the definitive source for information about the entire range of religious and social changes that altered the face of Europe in the sixteenth century, encompassing not only issues of church polity and theology but also developments in politics, economics, demographics, art and literature. This broadly cast, interdisciplinary definition allows for a comprehensive social and intellectual history of early modern Europe.